Severity of Ionized Hypercalcemia and Hypocalcemia Is Associated With Etiology in Dogs and Cats - Coady, Michelle; Fletcher, Daniel J.; Goggs, Robert (Frontiers in Veterinary Science, 2019)
Background: Calcium disorders are common in small animals, but few studies have investigated the etiology of ionized hypercalcemia and hypocalcemia in large populations. This study aimed to determine the incidence of ionized calcium disorders in dogs and cats treated at a tertiary referral clinic and to describe the associated diseases. Methods: An electronic database of electrolyte analyses conducted at the Cornell University Hospital for Animals from 2007-2017 was searched. Dogs and cats with ionized hypercalcemia or hypocalcemia were identified based on institution reference intervals. Duplicate case entries were removed. Medical records were reviewed to identify the cause of the calcium abnormality. Chi-squared analysis with Bonferroni adjustment was performed to compare frequencies of disease processes between mild and moderate-severe disturbances. Results: The database included 15,277 dogs and 3,715 cats. Hypercalcemia was identified in 1,641 dogs and 119 cats. The incidence of canine and feline hypercalcemia was 10.7% and 3.2% respectively. Hypocalcemia was identified in 1,467 dogs and 450 cats. The incidence of canine and feline hypocalcemia was 9.6% and 12.1% respectively. The most common pathologic causes of hypercalcemia in dogs were malignancy-associated (12.9%), parathyroid-dependent (4.6%) and hypoadrenocorticism (1.7%). In cats, malignancy-associated hypercalcemia (22.7%), kidney injury (13.4%) and idiopathic hypercalcemia (12.6%) were most common. Dogs presenting with moderate-severe hypercalcemia versus mild hypercalcemia were significantly more likely to have hyperparathyroidism, malignancy-associated hypercalcemia or hypervitaminosis D, whereas cats were significantly more likely to have malignancy-associated hypercalcemia or idiopathic hypercalcemia. The most common pathologic causes of hypocalcemia in dogs were critical illness (17.4%), kidney injury (10.4%) and toxicity (7.5%). In cats, kidney injury (21.6%), urethral obstruction (15.1%), and critical illness (14.7%) were most frequent. Dogs presenting with moderate-severe hypocalcemia were significantly more likely to have hypoparathyroidism, kidney injury, eclampsia or critical illness, whereas cats were significantly more likely to have kidney injury, soft tissue trauma or urethral obstruction. Conclusions: Mild calcium disturbances are most commonly associated with non-pathologic or transient conditions. Malignancy-associated hypercalcemia is the most common cause of ionized hypercalcemia in dogs and cats. Critical illness and kidney injury are frequent causes of ionized hypocalcemia in both species.